Charlotte Bronte - Jane Eyre - Lodge, Sara,Tredell, Nicolas (Macmillan Education UK, 2009)
Cover – Contents – Acknowledgements – Introduction – CHAPTER ONE: Victorian Responses: Power and Popularity – Coarseness and Criticism – CHAPTER TWO: Jane Eyre's 'I': From Humanism to Deconstruction – CHAPTER THREE: An Iconic Text: Feminist and Psychoanalytic Criticism – CHAPTER FOUR: Caste Typing: Marxist and Materialist Criticism – CHAPTER FIVE: Bertha's Savage Face: Postcolonial Concerns – CHAPTER SIX: New Historicism and The Turn Toward History – CHAPTER SEVEN: Jane Eyre Adapted – Conclusion – Notes – A Brief Guide to Further Reading – Select Bibliography – Index – A – B – C – D – E – F – G – H – I – J – K – L – M – N – O – P – R – S – T – W – Y – Z.
Description based on publisher supplied metadata and other sources
Keywords: Governesses in literature; Electronic books